Assessing the energy implications of exploiting stormwater, through artificial aquifer recharge, as an alternative water source in the Cape Flats, South Africa - Gobin, Aumashvini (Energy Research Centre, 2018)
South Africa has been facing challenges in both its energy and water sectors over the past few years. They are heavily dependent on each other and a better understanding of the linkages between the two sectors is crucial for sustainable development and planning in both sectors. While the water-energy nexus has been widely explored in developed countries, there is a limited amount of literature found on the significance of the nexus in South Africa. With the current critical drought in the region, alternative water sources are being considered by the City of Cape Town including seawater desalination, water re-use and abstraction of groundwater, to increase potable water supplies. The Cape Flats Aquifer represents a significant water resource for Cape Town and its yield can be further augmented by using artificial recharge with stormwater. Due to the location and water quality of the resource, several possible approaches have been identified for its exploitation. This study investigates quantitatively the energy implications of the three selected approaches in order to exploit the Cape Flats Aquifer as an alternative water source for Cape Town and further provides the potential carbon emissions from their respective energy usages. The three approaches consist of a Centralised Approach to treat the abstracted water for potable uses at two existing Water Treatment Plants (Blackheath and Faure); a Decentralised Approach to supply neighbouring suburbs with minimally treated water for non-potable uses through four proposed treatment plants and a Desalination Approach to treat brackish groundwater to potable quality at a proposed desalination plant. The energy implications of the approaches were evaluated using both direct energy usage during the abstraction, conveyance and treatment stages and the embodied energy of the consumables used during the treatment processes. These were then used to compare the shares of direct electricity intensities and embodied energy intensities of the alternatives at each stage to determine their viability. The individual stages' and overall energy intensities were quantified in form of the total energy required to produce a kl of treated water. The minimum energy required to abstract and convey the water was estimated using basic hydraulic principles. The energy usage at treatment plant levels was computed using the installed electrical capacities at the two existing water treatments for the Centralised Approach while the Decentralised Approach's demand was estimated by determining the treatment processes required to produce non-potable water, which is fit for usage. Energy requirements at the desalination plant were estimated using the salinity levels of the brackish groundwater and target salinity concentration of the treated water. The energy intensities of the approaches were then used as a basis to calculate the current and future electricity costs and their associated carbon footprints using the CSIR (2016) least cost scenario and the IRP (2016) base case future electricity mixes, as the higher and lower threshold for electricity generation costs and carbon emissions. The study found that the electricity intensities of all three alternatives depended significantly on the spatial layout of their respective systems, that is, the topography, distance and extent of their transmission networks. However, the embodied energy intensity of the Centralised alternative was found to be comparable to its electricity intensity, since more chemicals were to purify the water to potable levels. The Decentralised Approach's extensive pumped transmission networks contributed the most to its electricity intensity during the treatment process. The Desalination option was found to be the most energy intensive alternative, with energy intensities ranging from 7.41 to 9.62 MJ/kl, of all three options (1.16 to 1.57 MJ/kl for the Centralised Approach and 3.57 to 7.31 MJ/kl for the Decentralised Approach) and had the highest costs and emissions intensities, mostly caused by the country's coal intensive electricity mix. The Centralised option was found to be the least energy and carbon intensive of the three options and the most viable approach investigated. Desalination, nonetheless, can still considered as an alternative, given the issue of water scarcity, to increase water supplies. Despite its high energy demands, its carbon footprint could potentially decrease with a larger uptake of renewable energy technologies as sources of electricity. The importance of holistic planning across sectors was brought out quantitatively by using current and future water and energy mixes, providing valuable insights on the water-energy nexus, in this study.